Application of Bio-Inspired Algorithms and Neural Networks for Optimal Design of Fractal Frequency Selective Surfaces - Silva, Paulo Henrique da Fonseca; Silva, Marcelo Ribeiro da; Nóbrega, Clarissa de Lucena; D’Assunção, Adaildo Gomes (IntechOpen, 2012)
None